2011
DOI: 10.1108/09513571111133045
|View full text |Cite
|
Sign up to set email alerts
|

University corporatisation

Abstract: Purpose -The purpose of this paper is to examine the work-related attitudes ( job satisfaction, job stress and the propensity to remain) of Australian academics and their association with organisational, institutional and demographic factors. Design/methodology/approach -Data were collected by distributing a survey questionnaire to 750 academics, from 37 Australian universities. Findings -The results indicate a moderately low level of job satisfaction, moderately high level of job stress, and high propensity t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(17 citation statements)
references
References 69 publications
(152 reference statements)
2
14
0
1
Order By: Relevance
“…The impact of ERA on UniA academics is consistent with the views of prior studies where various changes in policies by the government have had a negative impact on academics (NTEU ; Pop‐Vasileva et al. ). It also confirms the findings of studies that indicate increased academic workload and stress levels due to the various public sector reforms to which universities have been subjected over recent years (Winefield et al.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…The impact of ERA on UniA academics is consistent with the views of prior studies where various changes in policies by the government have had a negative impact on academics (NTEU ; Pop‐Vasileva et al. ). It also confirms the findings of studies that indicate increased academic workload and stress levels due to the various public sector reforms to which universities have been subjected over recent years (Winefield et al.…”
Section: Resultssupporting
confidence: 87%
“…Further, some studies also disclose that academics have been adversely affected by the various changes in the Australian HES (NTEU ; Pop‐Vasileva et al. ). It is, therefore, of interest to examine empirically the effect of internal research‐oriented PMS developed in response to ERA on the working life of academics.…”
Section: Review Of Literature On Commodification Of Labour and Performentioning
confidence: 99%
“…While these changes to the academic work environment have been general across faculties, it has been argued that business and accounting faculties have been most strongly affected because business schools in general, and accounting faculties in particular, have been subject to the greatest pressures of over‐enrolments and staff shortages leading to higher student/staff ratios and larger class sizes relative to other faculties (Pop‐Vasileva et al , 2011; Su and Baird, 2017; Steenkamp and Roberts, 2018; Hancock et al , 2019). With respect to the accounting faculty, it has also been argued that the pressure to publish in top‐tier accounting journals is more strongly felt than in other faculties because of the small number of such journals (Vesty et al , 2018).…”
Section: Introductionmentioning
confidence: 99%
“…There has been a number of studies in recent years of the adverse effects of these changes in the academic work environment on academics’ work‐related attitudes and their psychosocial and physical health. Those studies have generally found increasing levels of job stress and burnout and decreasing levels of job satisfaction and organisational commitment (e.g., Pop‐Vasileva et al , 2011; Su and Baird, 2017), as well as deleterious effects on wellbeing, work quality, and work‐life balance (e.g., Bell et al , 2012; Steenkamp and Roberts, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…At the institutional level, the funding implications of the research assessment exercise are important, since achieving a good rating can influence the level of university funding into the future (Agyemang and Broadbent, 2015). At the individual researcher level, although institutional pressures from government accountability and assurance measures have pressured academics to publish more (Villiers and Dumay, 2013), the 'audit culture' regime that has developed as a result (Verbeeten, 2008) has imposed on researchers both an implicit and explicit expectation that the practical significance of academic knowledge production is demonstrable (Pop-Vasileva, Baird, and Blair, 2011) to external organisations on which there is financial dependence (Broadbent, Gallop, and Laughlin, 2010). A number of disturbing consequences have been observed in response.…”
Section: Introductionmentioning
confidence: 99%